2020
DOI: 10.31014/aior.1992.03.01.193
|View full text |Cite
|
Sign up to set email alerts
|

nalysis of the Effect of Business Strategy and Financial Distress on Tax Avoidance

Abstract: The Journal of Economics and Business is an Open Access publication. It may be read, copied, and distributed free of charge according to the conditions of the Creative Commons Attribution 4.0 International license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
1
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 13 publications
6
19
1
13
Order By: Relevance
“…Despite the important role financial distress level in influencing companies' tax strategy, a limited number of studies are available to study such a relationship. Previous studies have found that a higher level of financial distress leads the companies to engage in aggressive tax planning (Cita & Supadmi, 2019;Edwards, Schwab, & Shevlin, 2016;Richardson, Taylor, & Lanis, 2015;Sadjiarto et al, 2020) as they require high cash holding to continue operations. Since a higher level of financial distress reduces the amount of tax paid by the companies, the presence of NAS fee in such companies is expected to have a significant influence on the companies' aggressive tax planning activities.…”
Section: The Influence Of Nas Fee On the Relationship Between Financial Distress And Aggressive Tax Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the important role financial distress level in influencing companies' tax strategy, a limited number of studies are available to study such a relationship. Previous studies have found that a higher level of financial distress leads the companies to engage in aggressive tax planning (Cita & Supadmi, 2019;Edwards, Schwab, & Shevlin, 2016;Richardson, Taylor, & Lanis, 2015;Sadjiarto et al, 2020) as they require high cash holding to continue operations. Since a higher level of financial distress reduces the amount of tax paid by the companies, the presence of NAS fee in such companies is expected to have a significant influence on the companies' aggressive tax planning activities.…”
Section: The Influence Of Nas Fee On the Relationship Between Financial Distress And Aggressive Tax Planningmentioning
confidence: 99%
“…Companies that are deemed to be socially responsible are expected to comply with the tax law and pay the fair amount of tax (Salihu, Annuar, Normala, & Obid, 2015). However, as tax has always been seen as a burden, companies tend to utilize any opportunity to reduce the tax, for example by employing various tax planning strategies (Dhamara & Violita, 2018;Eskandar & Ebrahimi, 2020;Mgammal, 2015;Oktaviyani & Munandar, 2017;Sadjiarto, Hartanto, Natalia, & Octaviana, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Kajian terhadap hubungan antara kesulitan keuangan dan penghindaran pajak, telah dilakukan beberapa dengan objek yang berbeda. Di antara temuannya menunjukkan bahwa kesulitan keuangan secara signifikan dan positif berdampak terhadap penghindaran pajak (Richardson et al, 2015;Sadjiarto et al, 2020). Kajian empiris lain menyajikan bukti empiris yang menyatakan tidak adanya pengaruh faktor kesulitan keuangan terhadap penghindaran pajak.…”
Section: H1cunclassified
“…Dalam kondisi semacam ini, perusahaan relatif untuk menghindari hal-hal yang dapat memperburuk citra perusahaan, yang salah satunya adalah upaya penghindaran pajak (Cita & Supadmi, 2019). Temuan ini bertentangan dengan temuan penelitian sebelumnya yang menyimpulkan adanya pengaruh positif antara kesulitan keuangan perusahaan terhadap penghindaran pajak (Richardson et al, 2015;Sadjiarto et al, 2020).…”
Section: Rokhaniyahunclassified
“…Research with the dependent variable of tax avoidance has been carried out, both from within the country and abroad. Research conducted in Indonesia related to this topic has been carried out by Marfirah and Syam BZ, (2016), Meilia and Adnan, (2017), Alifianti, et al, (2017), Rani, (2017, Dhamara and Violita, (2017) , Wardani and Khoiriyah, (2018), Fathorrahman andSyaiful, (2019), Windyasari, et al, (2019), Pratiwi, http://eduvest.greenvest.co.id et al, (2020), Purba, et al, (2020), Nurrahmi and Rahayu, (2020), Harianto, (2020), Anggraini, et al, (2020 and Sadjiarto, et al, (2020). Meanwhile, research conducted by foreign researchers, namely Armstrong, et al, (2015), Higgins, et al, (2015), Edwards, et al, (2016), Tilehnouei, et al, (2018, Jiménez-Agueira, ( 2018), Martinez andFerreira, (2019), Kalil, (2019) and Dhawan, et al, (2020).…”
Section: Introductionmentioning
confidence: 99%